2018
DOI: 10.1029/2018jd028506
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Improvement of Subseasonal Prediction in the National Centers for Environmental Prediction Global Ensemble Forecast System

Abstract: In order to provide ensemble-based subseasonal (weeks 3 and 4) forecasts to support the operational mission of the Climate Prediction Center, National Centers for Environmental Prediction, experiments have been designed through the Subseasonal Experiment (SubX) project to investigate the predictability in both tropical and extratropical regions. The control experiment simply extends the current operational Global Ensemble Forecast System (GEFS; version 11) from 16 to 35 days. In addition to the control, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Here, we assess the application of EMOS and two machine learning post-processing methods to 1-35 day forecasts of the 2-m maximum air temperature for all land grid points over East Asia • N, 70-140 • E) using the raw ensemble forecast from EMC-GEFS described by Zhu [44]. The calendar year 2016 is used as the validation period.…”
Section: Verification Methodsmentioning
confidence: 99%
“…Here, we assess the application of EMOS and two machine learning post-processing methods to 1-35 day forecasts of the 2-m maximum air temperature for all land grid points over East Asia • N, 70-140 • E) using the raw ensemble forecast from EMC-GEFS described by Zhu [44]. The calendar year 2016 is used as the validation period.…”
Section: Verification Methodsmentioning
confidence: 99%
“…Zampieri et al (2018) indicate high potential for sea ice prediction in the sub-seasonal timescales, especially for late summer forecasts, and advocate the need to reduce systematic seasonally dependent model biases and develop advanced DA capabilities to constrain sea ice extent and sea ice thickness. Zhu et al (2018) showed that MJO forecast skill can be improved in the NCEP Global Ensemble Forecast System (GEFS) from an average of 12.5 days (control) to nearly 22 days by (1) adding stochastic physical perturbations, (2) considering ocean impacts by using a two-tiered sea surface temperature approach (combing an analysis product with a forecast of SST from a coupled model), and (3) applying a new scale-aware convection scheme to improve the model physics for tropical convection. They also showed improved ensemble mean anomaly correlation of 500-hPa geopotential height in the extratropics over weeks 3 and 4.…”
Section: Prediction At Subseasonal To Seasonal Timescalesmentioning
confidence: 99%
“…The atmospheric model is the NAVy Global Environmental Model (NAVGEM) (Hogan, 2014), and the ocean and sea ice models are part of the Global Ocean Forecasting System version 3.1 (GOFS 3.1) (Metzger et al, 2014). Navy‐ESPC is unique compared to many other global coupled modeling systems (Infanti & Kirtman, 2016; Lin et al, 2016; Saha, 2014; Sun et al, 2018; Vitart et al, 2017; Zhu, 2018) in that the ocean model horizontal resolution is eddy resolving in both the ensemble (i.e., probabilistic) and deterministic configurations. In many operational coupled modeling systems, the ocean and sea ice components are included primarily to provide better atmospheric bottom/surface boundary conditions but only at eddy‐permitting resolution (~1/4° or coarser).…”
Section: Introductionmentioning
confidence: 99%